OUTCOME OF USE OF NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE THROUGH INFANT FLOW DRIVERS IN NEONATES WITH RESPIRATORY DISTRESS IN A TERTIARY CARE HOSPITAL IN PAKISTAN - Anwaar, Osama; Hussain, Mudassar; Shakeel, Maria; Baig, Mirza Muhammad Ahsan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Nasal continuous positive pressure has been used for management of respiratory distress in neonates in various conditions as a primary modality. Objective of the study is to evaluate the frequency of improved outcome and complications of use of nasal CPAP through infant flow drivers in neonates with respiratory distress. The study was conducted from 2nd April 2017 to 2nd October 2017 in neonatal intensive care unit of Allama Iqbal Memorial Teaching Hospital Sialkot. Methods: All neonates with respiratory distress fulfilling the clinical criteria (Neonates with gestational age 28 weeks to 40 weeks having clinical signs of respiratory distress classified according to down score (tachypnea, grunting, decreased air entry, cyanosis, recessions), neonates having pc02 <60 mmhg, neonates having x-ray findings consistent with respiratory distress syndrome (RDS), Transient tachypnea of newborn (TTN) and pneumonia) were included in the study. Nasal CPAP was used at variable settings. Outcome, complications, indications, associated diseases and hospital stay along with other baseline characteristics were assessed. Success was defined as improvement of the respiratory distress as assessed by down score, maintenance of SPO2 above 90% in room air after weaning from CPAP for about consecutive 4 hours and normalization of blood gases while the failure as need for mechanical ventilation. Results: Total 60 neonates were included in the study. Mean weight was 2113.3±580.32 g while mean gestational age was 33.35±2.59 weeks. Total 52 (86.7%) babies were successfully weaned off from nCPAP while only 8 (13.3%) neonates required mechanical ventilation. Main indication of use of CPAP was RDS (65%). No complications were observed in 73.3% babies while 26.7% had complications of which nasal deformities accounted for 20% and abdominal distension for 6.37%. Conclusion: Nasal CPAP can be safely and easily used as primary support for neonates with respiratory distress even in resource limited developing countries. It reduces the need for mechanical ventilation and thus hospital stay. Keywords: Continuous positive airway pressure; Noninvasive ventilation; Respiratory distress Syndrome; Developing countries